Establecimiento de cultivos de células en suspensión de Lavandula angustifolia Miller - Flores García, Edson Missael (Universidad Autónoma Metropolitana, 2013)
Lavandula angustifolia is a plant native to Europe, belongs to the family of Lamiaceae, produces a variety of secondary metabolites that have uses in the cosmetics, pharmaceutical and even recently in the beekeeping precisely because its essential oils. However, it is at the merey of weather events, as well as sorne pests and diseases affecting crops severely open. Moreover, the suspension cell culture has become a tool for biotechnology and sustainable species preservation, large scale production of commercially important plants and metabolites. In this study, the establishment of cell suspension culture of L. angustifolia, first plant was collected in the chinampas of Xochimilco, acclimated to the conditions of the UAM-1, from her young leaf explants were removed and cultured aseptically on Murashige and Skoog (MS) supplemented with a synthetic auxin (2,4-D) at a concentration of 6.79 mM to induce callus formation . Friable callus were placed on MS medium flasks with the same concentration of 2,4-D, until the homogenization was obtained cell line and suspension cultures, leaf samples of callus and suspension were analyzed by thin layer chromatography (TLC). Two phenotypes were obtained with a yield of callus induction of 95.22% (callus callus yellowish light brown and clear) from leaf explants of L. angustifolia treated with 6.79 mM 2,4-D, the callus formed by the explant is initially grayish white and fractions of this callus subsequently become light brown, hence the same cell line derived two different phenotypes . The clear yellow callus line and is not displayed oxidation friable why was selected to set the suspension culture. TLC analysis of extracts of callus light brown, light yellow callus and suspension culture showed the presence of compounds having an Rf = 0.26 similar among themselves but different from linalool Rf = 0.53, though in suspension cultures also observed increased presence of other compounds compared with extracts of leaf and callus.; Lavandula angustifolia es una planta originaria de Europa, pertenece a la familia de las Lamiaceas, produce una gran variedad de Metabolitos secundarios que tienen usos en la industria cosmética, farmacéutica e incluso últimamente en la apícola precisamente por sus aceites esenciales. Sin embargo, se encuentra a merced de eventos cl imáticos, así como de algunas plagas y enfermedades que afectan severamente los cultivos a cielo abierto. Por otro lado, el cultivo de células en suspensión se ha convertido en una herramienta biotecnológica y sustentable para la preservación de especies, producción a gran escala de plantas de interés comercial y de Metabolitos. En este trabajo se estudió el establecimiento de cultivo de células en suspensión de L angustifolía, primeramente, se recolectó la planta en la zona chinampera de Xochimilco, se aclimató a las condiciones de la UAM-1, de ella se extrajeron explantes foliares jóvenes y se cultivaron asépticamente en medio de cultivo Murashige y Skoog (MS), suplementado con una auxina sintética (2,4-0) a una concentración de 6.79 µM para inducir la formación de callo. Los callos friables se colocaron en matraces con medio MS y con la misma concentración de 2,4-0, hasta que se obtuvo la homogenización y línea celular de cultivos en suspensión; muestras de hoja, de callo y de suspensión fueron analizadas por cromatografía de capa fina (TLC). Se obtuvieron dos fenotipos de callo con un rendimiento de inducción del 95.22% (callo café claro y callo amarillento claro) a partir de los explantes foliares de L. angustifolia tratados con 2,4-D 6.79 µM; el callo formado por el explante en un inicio es de color blanco grisáceo y posteriormente fracciones de este callo se tornan color café claro, de ahí que de la misma línea celular se deriven dos fenotipos diferentes. La línea de callo amarillento claro no presentó oxidación y es friable motivo por el cual se seleccionó para establecer el cultivo en suspensión. El análisis por TLC de los extractos del callo café claro, callo amarillento claro y cultivo en suspensión muestran la presencia de compuestos que tienen un Rf = 0.26 similar entre sí mismos pero diferente al del linalol Rf = 0.53, sin embargo en los cultivos en suspensión se observa también mayor presencia de otros compuestos comparados con extractos de hoja y de callo.